Authoritative Approach and Student Empowerment Among University Students. (13th May 2015) - Cakır, S. Gulfem
Abstract: This study examines the role of instructors' authoritative attitudes on learner empowerment among university students. Study sample comprised of 322 university students attending a faculty of education in Turkey. Their ages ranged from 17-25 years (mean age: 20.34 years). Multiple regression analysis results suggested that authoritative attitudes of the instructors positively predicted all three dimensions of learner empowerment. More specifically, instructors' authoritative attitudes accounted for the largest variance in meaningfulness (48.8%), followed by impact (21.4%) and competence (13.2%). These results suggested that instructors' authoritative approaches to the classroom management have impact on learner empowerment.